PERAN HUMAS BADAN PELINDUNGAN PEKERJA MIGRAN INDONESIA (BP2MI) DALAM MEMBANGUN KEPERCAYAAN CALON PEKERJA MIGRAN - Bosya Fitra Perdana (2023)
Negative stereotypes towards migrant workers still exist in society. Migrant workers often face mistreatment and are predominantly employed as domestic helpers. This research aims to understand how the Public Relations (PR) conducted by the Organization provides information to build trust among prospective migrant workers. The research utilizes a qualitative descriptive method, which formulates research questions to explore and describe the social situation in depth and comprehensively. The theory employed is Organizational Information (Information Environment, Information Uncertainty, Rules, and Cycles). Key informants and informants are purposively selected. Data is collected through interviews with the Head of Public Relations Department at BP2MI (Indonesian Migrant Workers Protection Agency), PR professionals, and prospective Indonesian migrant workers. The research findings indicate that BP2MI's PR prioritizes disseminating information about BP2MI's programs through socialization, social media, and the agency's website. Although social media has not achieved the desired effectiveness, BP2MI's website serves as a reference for prospective migrant workers to obtain information. Addressing complaints is key to building trust; BP2MI's PR has a system in place to receive complaints through official channels (Public Information and Documentation Center and Website) as well as unofficial channels (Social Media). Assessing BP2MI's reputation is still challenging for its PR; however, positive sentiments expressed by the media and the increasing number of registered migrant workers contribute to the agency's growing reputation.